Efficacy and retention rate of secukinumab in psoriatic arthritis across different clinical phenotypes: insights from the Italian GISEA Registry - Giuseppe Lopalco; Maria Morrone; Fabiola Atzeni; Chiara Bazzani; Francesco Paolo Bianchi; Francesco Paolo Cantatore; Roberto Caporali; Antonio Carletto; Alberto Cauli; Maria Sole Chimenti; Sergio Colella; Fabrizio Conti; et al. (Therapeutic Advances in Musculoskeletal Disease)
Background: Randomized clinical trials have demonstrated the efficacy of secukinumab (SECU) in reducing disease activity in psoriatic arthritis (PsA), while real-world studies prove a broader perspective on SECU’s usefulness in everyday clinical practice. Objectives: To assess the effectiveness of SECU by evaluating drug survival and identifying potential predictors of clinical response and treatment discontinuation in patients with moderate-to-severe PsA, using real-world data from the Italian Group for the Study of Early Arthritis (GISEA) registry. Design: This longitudinal retrospective study included PsA patients treated with SECU, spanning from May 2016 to November 2023. Methods: Data from 1045 PsA patients, including 783 with peripheral-only PsA (perPsA) and 262 with peripheral and axial involvement (mixed PsA) were analyzed. Drug survival was estimated by Kaplan–Meier analysis. Clinical outcomes, including Disease Activity Index for Psoriatic Arthritis (DAPSA), Psoriasis Area Severity Index (PASI), Ankylosing Spondylitis Disease Activity Score (ASDAS, C-Reactive Protein (CRP)-based), and Visual Analogue Scale (VAS) measures, were evaluated at baseline and at 6, 12, and 24 months. Adjusted hazard ratios (aHRs) for discontinuing SECU were determined using multivariate Cox regression models. Results: SECU survival at 24 months was 63.24%, significantly higher in mixed PsA compared to perPsA ( p  = 0.036). In the overall PsA population, DAPSA scores decreased significantly at 6 months, and further at 24 months (all p  < 0.0001). In mixed PsA, ASDAS-CRP scores were significantly reduced at 6 months and remained stable through 24 months (all p  < 0.0001). VAS pain scores also improved already at 6 months and continued to improve at 24 months (all p  < 0.0001). Higher age (aHR = 0.98, 95% confidence interval (CI): 0.96–0.99, p  = 0.007) and lower baseline DAPSA scores (aHR = 1.02, 95% CI: 1.01–1.03, p  = 0.014) were associated with greater persistence of SECU treatment. SECU was well tolerated, with no serious adverse events. Conclusion: SECU showed sustained clinical improvements in both peripheral and axial involvement of PsA patients over 24 months, with higher persistence observed in mixed PsA patients. Our findings highlight the favorable clinical and safety profile of SECU in real world.